Post translational modifications at the verge of plant-geminivirus interaction - Prasad, Ashish; Sharma, Shambhavi; Prasad, Manoj (Biochimica et biophysica acta. Gene regulatory mechanisms, 2023)
Plant-virus interaction is a complex phenomenon and involves the communication between plant and viral factors. Viruses have very limited coding ability yet, they are able to cause infection which results in huge agro-economic losses throughout the globe each year. Post-translational modifications (PTMs) are covalent modifications of proteins that have a drastic effect on their conformation, stability and function. Like the host proteins, geminiviral proteins are also subject to PTMs and these modifications greatly expand the diversity of their functions. Additionally, these viral proteins can also interact with the components of PTM pathways and modulate them. Several studies have highlighted the importance of PTMs such as phosphorylation, ubiquitination, SUMOylation, myristoylation, S-acylation, acetylation and methylation in plant-geminivirus interaction. PTMs also regulate epigenetic modifications during geminivirus infection which determines viral gene expression. In this review, we have summarized the role of PTMs in regulating geminiviral protein function, influence of PTMs on viral gene expression and how geminiviral proteins interact with the components of PTM pathways to modulate their function. •Post-translational modifications (PTMs) govern protein structure, function and stability.•Geminiviral proteins are subject to PTMs and this has a major influence on viral resistance/susceptibility in hosts.•Geminiviruses influence host PTM machinery to promote their own replication and gene expression.•Studies on PTMs other than phosphorylation and ubiquitination are limited.